Fasad Timpanum Bangsal Tosan Mangkunegaran Menepis Spekulasi Apropriasi Religi - Aribowo, Widodo (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
This research aims to answer a puzzle that has remained unanswered for decades due to the disconnection of oral stories about the facade structure of Bangsal Tosan at Pendopo Ageng Mangkunegaran Palace. This article aims to examine the appearance of the facade structure and the ornaments on it, in relation to the speculation of religious appropriation in the facade structure. The descriptive method within the constructivism paradigm is applied based on the findings of data deemed adequate for the formation of a clarificative narrative about the structure. It is called clarificative because it is an explanation of why there is a triangular structure (timpanum) and a Western-style relief on the facade, both of which are not commonly found in traditional Javanese buildings. This research produces a narrative explanation that the timpanum facade and Western-style reliefs on Pendopo Ageng of Mangkunegaran Palace were made during the time of K.G.P.A.A. Mangkunagara IV and named Bangsal Tosan. Although Western in style, the facade and ornaments are symbols of Javanese culture such as panembarama (greeting), acknowledgement of supernatural powers, and hopes for prosperity. The spectacular palace art structure is interpreted as the emergence of secular high fashion, a statement of the Mangkunegaran Palace's identity as the palace of an important person (pangeran) but not a king. This finding has the potential to change or otherwise enrich theories about the sacredness of palace buildings. Instead of practising strict and obedient social religious practices, Mangkunagara IV innovated the Tosan Ward in the Mangkunegaran Palace.